Analysis on the management strategy of happiness education based on human-oriented care - Le Kang; Chantana Viriyavejakul; Ampapan Tuntinakhongul (My University, 2024)
This study aims to explore happiness education management strategies for engineering students based on person-centered care. The research adopts a mixed-methods approach, combining quantitative and qualitative research. In the quantitative phase, a sample of 300 engineering students is recruited through a questionnaire survey. In the qualitative phase, 15 engineering students participate in semi-structured interviews, and 2 focus groups are conducted. The research results indicate differences among engineering students in dimensions of happiness, such as positive emotions, self-satisfaction, social support, and academic satisfaction. The application of person-centered care in happiness education has a positive impact on students’ learning motivation, emotional identity, and self-satisfaction. Additionally, current happiness education management strategies have achieved certain results in emotional management and social support but still have room for improvement in personalized support and care. Strategies based on person-centered care show significant advantages in multiple dimensions, comprehensively meeting the emotional and social needs of engineering students and enhancing their happiness levels. The findings of this study highlight the crucial role of person-centered care in happiness education for engineering students. It is recommended to strengthen the integration of person-centered care principles, provide diversified emotional management support, enhance the construction of social support networks, develop personalized happiness education plans, and continually assess and improve the effectiveness of strategies. These recommendations will contribute to optimizing happiness education management for engineering students, promoting their comprehensive development and growth.
Keywords: Educational Reforms and Innovations